2021
DOI: 10.3390/biomedicines9010036
|View full text |Cite
|
Sign up to set email alerts
|

Can Exercise-Induced Muscle Damage Be a Good Model for the Investigation of the Anti-Inflammatory Properties of Diet in Humans?

Abstract: Subclinical, low-grade, inflammation is one of the main pathophysiological mechanisms underlying the majority of chronic and non-communicable diseases. Several methodological approaches have been applied for the assessment of the anti-inflammatory properties of nutrition, however, their impact in human body remains uncertain, because of the fact that the majority of the studies reporting anti-inflammatory effect of dietary patterns, have been performed under laboratory settings and/or in animal models. Thus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 281 publications
(225 reference statements)
1
17
0
Order By: Relevance
“…Intense resistance training is known to increase muscle mass, strength/power, muscle protein synthesis, fibre cross-sectional area, 44,[57][58][59][60] running pace, and economy and to induce specific training adaptations to the mechanisms controlling the extent and time course of exercise-induced muscle damage. 61,62 These findings, combined with this study's results, suggest that due to their greater metabolic and neuromuscular adaptations, faster master mountain runners exhibit almost the same energy expenditure as slower runners. However, because they cover the distance in less time, they have fewer gait cycles.…”
Section: Discussionsupporting
confidence: 64%
“…Intense resistance training is known to increase muscle mass, strength/power, muscle protein synthesis, fibre cross-sectional area, 44,[57][58][59][60] running pace, and economy and to induce specific training adaptations to the mechanisms controlling the extent and time course of exercise-induced muscle damage. 61,62 These findings, combined with this study's results, suggest that due to their greater metabolic and neuromuscular adaptations, faster master mountain runners exhibit almost the same energy expenditure as slower runners. However, because they cover the distance in less time, they have fewer gait cycles.…”
Section: Discussionsupporting
confidence: 64%
“…Our group has recently shown that individuals experiencing the highest reductions in Type IIx %CSA and concomitant increases in Type IIa %CSAs are those with the greatest improvements in their lipid profile after 10 weeks of resistance training [12]. Indeed, as muscle is a highly plastic tissue [45,[56][57][58][59][60], its properties can be changed according to nutrition but mostly to training-induced metabolic, physiological and mechanical stress. Increased training volumes upregulate molecular pathways controlling the size, type and metabolic procedures of muscle fibers, which ultimately results in the transmission of Type IIx to the more metabolically efficient Type IIa muscle fibers [4,5,7,12,45,56], changes that are highly related to those of lipidemic profiles [12].…”
Section: Gaps In Our Knowledge -Future Directionsmentioning
confidence: 99%
“…Regarding bioenergetics, glucose and lipids metabolism is upregulated during endurance exercise [ 28 , 29 , 30 , 31 , 32 , 33 ]. Additionally, long-term, regular endurance training results in volume (total distance or training duration per week) dependent, beneficial and specific adaptations on glucose and lipids metabolism, leading to completely different metabolic procedures and functionalities of glucose and lipids metabolic pathways than those observed in sedentary individuals [ 28 , 34 , 35 , 36 , 37 , 38 ]. For example, according to the “athletes’ paradox” phenomenon, even though endurance athletes possess increased intramuscular lipids concentrations, their insulin sensitivity is enhanced, a phenomenon attributed to the high daily metabolic demands during and after training bouts but primarily to the training-specific adaptions in oxidative capacities of their muscle fibers [ 15 ].…”
Section: Introductionmentioning
confidence: 99%